SOME FEATURES OF IMMUNE STATUS IN THE CHILDREN WITH CHRONIC TONSILLITIS - O. V. Sorokin; E. V. Markova; V. V. Abramov; V. A. Kozlov (Медицинская иммунология, 2014)
Abstract. The article provides some characteristics of immune status in the children suffering from chronic tonsillitis. Gender-associated peculiarities are taken into account, and comparative efficiency of certain rehabilitative therapeutic approaches is demonstrated for the children with different recurrence rates of this disorder.